ANALISIS PENERAPAN PRODUKSI BERSIH PADA INDUSTRI MINUMAN NATA DE COCO: Analysis of the Application of Clean Production in The Nata De Coco Beverage Industry - Reskiati Wiradhika Anwar; Rafika Ratik Srimurni; Wilda Harlia Devita; Dina Yuliasty Lamefa (Universitas Darussalam Gontor, 2022)
The nata de coco beverage processing process produces waste trash in the form of liquid and solid, which is if not properly handled, it can pollute the environment. Proper handling is requires to manage the waste so that it not only lowers the negative impact it has on the environment, but also has a beneficial impact on profit. Cleaner production is an option solution for achieving an environmentally sustainable industry by increasing productivity, maximizing the use of raw resources and reducing waste. In this research, an analysis of the implementation of cleaner production in the nata de coco beverage industry in Bogor City was conducted in numerous stages, including: preparation, planning and organization, process identification, feasibility evaluation, and determination of alternative strategies. Which purpose is to be able to make recommendations in the implementation of cleaner production for industries that are utilized and gain profit on it. From this research, it can be concluded that the underlying aspect is the technical factor from the housekeeping side, which covers the arrangement and preparation of the production flow starting from the purchasing and distribution of raw materials to the technical allocation of products. Handling waste that has gone unnoticed is also a problem in order to improve the cleanliness of the industrial site.